2014
DOI: 10.1016/j.egypro.2014.10.209
|View full text |Cite
|
Sign up to set email alerts
|

Two Dimension Numerical Modeling of Receiver Tube Performance for Concentrated Solar Power Plant

Abstract: In solar concentrators plants the vacuum receiver tube is considered the heart of the solar concentrator plant. The EES program was used to study both the effect of the annular pressure between the receiver tube and the envelope glass cover on the tube performance in terms of amount of collected energy, energy losses, temperature rise of the heat transfer fluid and the thermal efficiency of the receiver tube. The radiation and convection heat transfer between the outer surface of the receiver tube and the inne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…2. The energy transferred by conduction, radiation and convection from the absorber tube to the glass cover and the heat transfer fluid HTF was also simulated using the energy balance equations for each of the steel tube, glass cover and the HTF [16]. The model simulate the heat losses from the absorber tube to the glass cover by radiation and convection methods also simulate the heat losses by conduction through the glass cover from the inner to the outer surface.…”
Section: A Modeling Of Ptcmentioning
confidence: 99%
“…2. The energy transferred by conduction, radiation and convection from the absorber tube to the glass cover and the heat transfer fluid HTF was also simulated using the energy balance equations for each of the steel tube, glass cover and the HTF [16]. The model simulate the heat losses from the absorber tube to the glass cover by radiation and convection methods also simulate the heat losses by conduction through the glass cover from the inner to the outer surface.…”
Section: A Modeling Of Ptcmentioning
confidence: 99%
“…The optical performance analysis on PTC by Jebasingh et al [43] showed that the optical efficiency should be optimized to withstand against environmental conditions, many optical factors have been studied to improve the heating conditions of the absorber tube [44]. To reduce the temperature gradient of the absorber tube, scholars also have conducted many studies on certain specific heat transfer processes in PTR technology [45][46][47]. A new type of perforated plate inserts was proposed for use in parabolic trough collector, and the thermodynamic performance of the system was simulated [48].…”
Section: Introductionmentioning
confidence: 99%
“…The model has been based on the absorber tube wall temperature instead of fluid bulk temperature. The effect of the annular pressure between the absorber tube and the glass cover of the receiver tube on the tube performance was investigated by Ahmed [15]. The investigating included the amount of energy gained, the temperature rise of the heat transfer fluid (HTF), energy losses and efficiency.…”
Section: Introductionmentioning
confidence: 99%